Narrowband interference in pilot symbol assisted OFDM systems. - Coulson, A.J (IEEE Transactions on wireless communications)
The effect of narrowband interference on pilot symbol assisted detection and synchronization is discussed. It is shown both analytically and by computer simulation that pilot symbol detectors are particularly susceptible to narrowband interference. It is shown also that pilot symbol assisted frequency offset estimation is detrimentally affected by narrowband interference. The normalized least mean squares (N-LMS) adaptive noise cancellation algorithm, with only a small number of filter taps, is shown to perform well in suppressing narrowband interference in pilot symbol detectors. The combination of two-stage detection and the N-LMS algorithm is shown to be effective in producing interference-tolerant pilot symbol detection in OFDM systems.